Positive electrode material, method for preparing the same, and battery

CN120674459BActive Publication Date: 2026-10-27JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510677654.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2026-10-27
Estimated Expiration
2045-05-23

AI Technical Summary

Technical Problem

但是相对其他正极材料,如三元正极(NCM),LiFePO4的电化学能量比较低

Benefits of technology

在本申请实施例中,所提供的正极材料内核包括LiMn1-xVxPO4和Li3V2-yMny(PO4)3,Li3V2(PO4)3具有三维锂离子扩散通道,其锂离子扩散系数(10-9~10-10cm2·s-1)比LiMnPO4(10-15cm2·s-1)高至少五个数量级,具有较好的倍率性能和较高的电化学活性。将LiMnPO4与其复合,可以利用Li3V2(PO4)3提升LiMnPO4的电化学活性,且部分Mn与V还可以相互掺杂,从而整个LiMnPO4与Li3V2(PO4)3的复合材料的电化学性能得以提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120674459B_ABST
    Figure CN120674459B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a positive electrode material, a preparation method thereof and a battery. The positive electrode material comprises: an inner core and a carbon coating layer coated on at least part of the surface of the inner core; wherein the inner core comprises LiMn 1‑x V x PO4 and Li3V 2‑y Mn y (PO4)3; wherein 0<=x<=0.1 and 0<=y<=0.15. The positive electrode material has good rate performance, cycle stability and a high theoretical capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a cathode material, its preparation method, and a battery. Background Technology

[0002] In recent years, with the continuous development of science and technology and the economy, the demand for high-efficiency energy storage batteries has been increasing. Lithium-ion batteries are currently the most widely used rechargeable batteries. The cathode material of a lithium-ion battery is one of its core components, directly determining the battery's energy density, cycle life, safety, and cost. Phosphoric acid-based cathode materials, due to PO4... 3- The strong covalent bonds in PO make the internal structure of this series of materials stable and provide high safety performance. Commercially available LiFePO4 is a typical example; the redox potential of LiFePO4 is 3.45 V (vs. Li). + / Li); theoretical specific capacity is 170 mAh g. -1 Currently, the research and development process of LiFePO4 is becoming increasingly mature, and it has already been used as the cathode material in lithium-ion batteries for commercial electric vehicles and hybrid vehicles. However, compared with other cathode materials, such as ternary cathodes (NCM), LiFePO4 has a relatively low electrochemical energy.

[0003] Therefore, there is an urgent need to provide a phosphoric acid-based cathode material with higher specific capacity and / or higher voltage. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a cathode material, a method for preparing the same, and a battery thereof, wherein the cathode material has higher specific capacity and higher voltage.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows: According to one aspect of this application, an embodiment of this application provides a cathode material, the cathode material comprising: a core and a carbon coating layer covering at least a portion of the surface of the core; The kernel includes LiMn 1-x V x PO4 and Li3V 2-y Mn y (PO4)3; Where 0≤x≤0.1, 0≤y≤0.15.

[0006] In some of these embodiments, the LiMn 1-x V x PO4, Li3V 2-y Mn yThe molar ratio of (PO4)3 to carbon is 1:1:(0.01~0.1).

[0007] According to another aspect of this application, an embodiment of this application provides a method for preparing a cathode material, comprising the following steps: mixing a manganese source solution and a vanadium source solution and then carrying out a hydrothermal reaction to obtain an intermediate Mn(VO3)2; The intermediate Mn(VO3)2, lithium source, phosphoric acid source, carbon source and acid source are mixed in a solvent to obtain a mixture, which is then ball-milled, sintered and ground to obtain the cathode material.

[0008] In some embodiments, the solvent in the manganese source solution includes water and / or an organic solvent.

[0009] In some embodiments, the molar concentration of the manganese source solution is 0.03 mol / L to 0.5 mol / L.

[0010] In some of these embodiments, the manganese source includes at least one of MnCl2, MnSO4, Mn(NO3)2, or Mn3(PO4)2.

[0011] In some embodiments, the solvent in the vanadium source solution includes water and / or an organic solvent.

[0012] In some embodiments, the molar concentration of the vanadium source solution is 0.06 mol / L to 1 mol / L.

[0013] In some embodiments, the vanadium source includes V₂O₃, VO₂, V₂O₄, V₂O₅, NH₄VO₃, and H₄V₂O. 10 At least one of V(OH)3, Na3VO4 or Na4V2O7.

[0014] In some of these embodiments, the hydrothermal reaction is carried out at a temperature of 170°C to 190°C for a duration of 1 hour to 30 hours.

[0015] In some of these embodiments, the molar ratio of the intermediate Mn(VO3)2, the lithium source, the phosphoric acid source, the carbon source, and the acid source is (1~5):(1~10):(1~10):(0.02~20):(2~20).

[0016] In some of these embodiments, the molar concentration of the intermediate Mn(VO3)2 in the mixture is 0.01 mol / L to 1 mol / L.

[0017] In some of these embodiments, the solvent includes water and / or an organic solvent.

[0018] In some embodiments, the carbon source includes at least one selected from polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan laurate, glucose, pitch, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinylpyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene, or aniline.

[0019] In some embodiments, the ball mill rotates at a speed of 300 rpm to 400 rpm for a time of 0.5 h to 9 h.

[0020] In some embodiments, the sintering is carried out under an inert atmosphere, and the sintering includes pre-firing and baking.

[0021] In some of these embodiments, the pre-firing temperature is 250°C to 450°C, and the time is 1 hour to 6 hours.

[0022] In some of these embodiments, the calcination temperature is 650°C to 750°C, and the time is 1 hour to 12 hours.

[0023] In some of these embodiments, the particle size of the milled product is 100nm≤Dv50≤50μm.

[0024] According to another aspect of this application, an embodiment of this application provides a battery including a positive electrode sheet, the positive electrode sheet including a positive electrode material, the positive electrode material being the aforementioned positive electrode material or a positive electrode material prepared according to the aforementioned preparation method.

[0025] Implementing the technical solution of the present invention has at least the following beneficial effects: In this embodiment, the provided cathode material core includes LiMn 1-x V x PO4 and Li3V 2-y Mn y (PO4)3, Li3V2(PO4)3 has a three-dimensional lithium-ion diffusion channel, and its lithium-ion diffusion coefficient (10) -9 ~10 -10 cm 2 ·s -1 ) than LiMnPO4(10 -15 cm 2 ·s -1 The efficiency is at least five orders of magnitude higher, exhibiting better rate performance and higher electrochemical activity. Combining LiMnPO4 with Li3V2(PO4)3 can enhance the electrochemical activity of LiMnPO4, and some Mn and V can also be interdoped, thereby improving the overall electrochemical performance of the LiMnPO4 / Li3V2(PO4)3 composite material.

[0026] Furthermore, because some Mn and V can be interdoped, the contact between the core materials is tighter, which reduces the surface energy of the core materials and makes the contact between the carbon coating layer and the core materials more stable. This prevents the carbon coating layer from detaching during long cycles, effectively avoiding electrolyte failure caused by direct contact between the core materials and the electrolyte, preventing polarization of the cathode material, and improving the cycle stability of the cathode material. Compared to the conventional LiMnPO4 and Li3V2(PO4)3 composite, the tighter contact makes it less likely for manganese in lithium manganese phosphate to dissolve. The smaller-scale, tighter contact significantly improves electronic and ionic conductivity. Moreover, the carbon coating layer of the cathode material can improve the electronic conductivity of the cathode material, forming a conductive network, and can also reduce charge transfer impedance, improving the overall rate performance of the cathode material.

[0027] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0028] Figure 1 The image shown is a scanning electron microscope (SEM) image of the cathode material provided in Embodiment 1 of the present invention. Detailed Implementation

[0029] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0030] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0031] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0032] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0033] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0034] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0035] Compared to ternary cathode materials, the existing commercially available LiFePO4 exhibits a relatively low electrochemical energy. In contrast, LiMnPO4 has a stable crystal structure and a theoretical specific capacity of 170 mAh g⁻¹. -1 However, its redox potential is 4.1 V (vs. Li). + / Li), its theoretical energy density is about 20% higher than that of LiFePO4 (LiMnPO4 697Wh kg). -1 LiFePO4 586 Wh kg -1 However, the electronic conductivity of LiMnPO4 is <10⁻⁶. -10 S· cm -1 The ion diffusion coefficient is approximately 5.1 × 10⁻⁶. -14 cm 2 · s -1 This results in conventionally prepared LiMnPO4 materials exhibiting very low activity, with charge-discharge specific capacities far below theoretical values. Furthermore, in the LiMnPO4 system, Mn... 2+ The low-spin configuration is prone to Jahn-Teller distortion, and the distortion of the material structure weakens the electrochemical cycling performance.

[0036] [Cathode Material] In view of this, embodiments of this application provide a cathode material, the cathode material comprising: a core and a carbon coating layer covering at least a portion of the surface of the core; Among them, the kernel includes LiMn 1-x V x PO4 and Li3V 2-y Mn y (PO4)3; Where 0≤x≤0.1, 0≤y≤0.15.

[0037] The aforementioned "carbon coating layer covering at least a portion of the surface of the core" means that the carbon coating layer can be disposed on a portion of the surface of the core or on the entire surface of the core. As in this embodiment, the carbon coating layer can cover the entire surface of the core. This application does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.

[0038] In this application, the cathode material core includes LiMn. 1-x V x PO4 and Li3V 2-y Mn y (PO4)3, Li3V2(PO4)3 has a three-dimensional lithium-ion diffusion channel, and its lithium-ion diffusion coefficient (10) -9 ~10 -10 cm 2 ·s -1 ) than LiMnPO4(10 -15 cm 2 ·s -1 The efficiency is at least five orders of magnitude higher, exhibiting better rate performance and higher electrochemical activity. Combining LiMnPO4 with Li3V2(PO4)3 can enhance the electrochemical activity of LiMnPO4, and some Mn and V can also be interdoped, thereby improving the overall electrochemical performance of the LiMnPO4 / Li3V2(PO4)3 composite material.

[0039] Furthermore, because some Mn and V can be interdoped, the contact between the core materials is tighter, which reduces the surface energy of the core materials and makes the contact between the carbon coating layer and the core materials more stable. This prevents the carbon coating layer from detaching during long cycles, effectively avoiding electrolyte failure caused by direct contact between the core materials and the electrolyte, preventing polarization of the cathode material, and improving the cycle stability of the cathode material. Compared to the conventional LiMnPO4 and Li3V2(PO4)3 composite, the tighter contact makes it less likely for manganese in lithium manganese phosphate to dissolve. The smaller-scale, tighter contact significantly improves electronic and ionic conductivity. Moreover, the carbon coating layer of the cathode material can improve the electronic conductivity of the cathode material, forming a conductive network, and can also reduce charge transfer impedance, improving the overall rate performance of the cathode material.

[0040] In this application, Mn and V doping refers to the process in which vanadium ions enter the lithium manganese phosphate unit cell to replace manganese atoms during crystal growth, and manganese ions enter the lithium vanadium phosphate unit cell structure to replace vanadium atoms, thus performing in-situ doping.

[0041] In some specific implementations, LiMn 1-x V x PO4, Li3V 2-y Mny The molar ratio of (PO4)3 to carbon is 1:1:(0.01~0.1). As an example, LiMn... 1-x V x PO4, Li3V 2-y Mn y The molar ratio of (PO4)3 to carbon can be any one of the following values: 1:1:0.01, 1:1:0.05, or 1:1:0.1, or any range between the two. Here, "carbon" refers to the carbon in the carbon coating layer, and all carbon is present in the carbon coating layer. If LiMn 1-x V x PO4 or Li3V 2-y Mn y If the proportion of any one component in (PO4)3 is too high, the structural stability between the two materials will decrease, leading to a decrease in cycle stability; if LiMn 1-x V x PO4 or Li3V 2-y Mn y If the proportion of any one component in (PO4)3 is too small, material shedding during the cycling process will cause a decrease in cycling performance. If the proportion of carbon is too large, it will reduce the system's energy and capacity density, and will also reduce the material's rate performance and specific capacity; if the proportion of carbon is too small, the material's conductivity will decrease.

[0042] Therefore, based on the above scheme, a cathode material is provided, comprising a core and a carbon coating layer covering at least a portion of the surface of the core. The LiMn in the cathode material core... 1-x V x PO4 and Li3V 2-y Mn y (PO4)3, in both materials, Li3V2(PO4)3 has a three-dimensional lithium-ion diffusion channel, and its lithium-ion diffusion coefficient (10) -9 ~10 -10 cm 2 ·s -1 ) than LiMnPO4(10 - 15 cm 2 ·s -1 The efficiency is at least five orders of magnitude higher, exhibiting better rate performance and higher electrochemical activity. Combining LiMnPO4 with Li3V2(PO4)3 can enhance the electrochemical activity of LiMnPO4, and some Mn and V can also be interdoped, thereby improving the overall electrochemical performance of the LiMnPO4 / Li3V2(PO4)3 composite material.

[0043] Furthermore, because some Mn and V can be interdoped, the contact between the core materials is tighter, which reduces the surface energy of the core materials and makes the contact between the carbon coating layer and the core materials more stable. This prevents the carbon coating layer from detaching during long cycles, effectively avoiding electrolyte failure caused by direct contact between the core materials and the electrolyte, preventing polarization of the cathode material, and improving the cycle stability of the cathode material. Compared to the conventional LiMnPO4 and Li3V2(PO4)3 composite, the tighter contact makes it less likely for manganese in lithium manganese phosphate to dissolve. The smaller-scale, tighter contact significantly improves electronic and ionic conductivity. Moreover, the carbon coating layer of the cathode material can improve the electronic conductivity of the cathode material, forming a conductive network, and can also reduce charge transfer impedance, improving the overall rate performance of the cathode material.

[0044] [Preparation methods for cathode materials] Based on the same inventive concept, this application provides a method for preparing a cathode material, including the following steps: mixing a manganese source solution and a vanadium source solution and then carrying out a hydrothermal reaction to obtain an intermediate Mn(VO3)2; The intermediate Mn(VO3)2, lithium source, phosphoric acid source, carbon source and acid source are mixed in a solvent to obtain a mixture, which is then ball-milled, sintered and ground to obtain the cathode material.

[0045] It should be understood that all the characteristics and advantages described above regarding "cathode materials" also apply to the "preparation method of cathode materials," and will not be repeated here.

[0046] In some specific embodiments, the solvent in the manganese source solution includes water and / or an organic solvent. Specifically, the organic solvent includes, but is not limited to, alcoholic organic solvents or ketone organic solvents. As an example, the organic solvent may be ethanol or acetone.

[0047] In some specific embodiments, when the solvent is a mixture of water and an organic solvent, the volume of water is ≥40%. As an example, when the solvent is a mixture of water and an organic solvent, the volume of water can be 40%, 50%, or 60%.

[0048] In some specific embodiments, the molar concentration of the manganese source solution is 0.03 mol / L to 0.5 mol / L. As an example, the molar concentration of the manganese source solution can be 0.03 mol / L, 0.1 mol / L, 0.5 mol / L, etc., or it can be a value within the above range, without being specifically limited here.

[0049] In some specific embodiments, the manganese source includes, but is not limited to, at least one of MnCl2, MnSO4, Mn(NO3)2, or Mn3(PO4)2. As an example, the manganese source may be MnCl2 or MnSO4.

[0050] In some specific embodiments, the solvent in the vanadium source solution includes water and / or an organic solvent. Specifically, the organic solvent includes alcoholic organic solvents or ketone organic solvents. As an example, the organic solvent may be ethanol or acetone.

[0051] In some specific embodiments, when the solvent is a mixture of water and an organic solvent, the volume of water is ≥40%. As an example, when the solvent is a mixture of water and an organic solvent, the volume of water can be 40%, 50%, or 60%.

[0052] In some specific embodiments, the molar concentration of the vanadium source solution is 0.06 mol / L to 1 mol / L. As examples, the molar concentration of the vanadium source solution is 0.06 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, etc., and of course, it can also be a value within the above range, without being specifically limited here.

[0053] In some specific embodiments, the vanadium source includes, but is not limited to, V₂O₃, VO₂, V₂O₄, V₂O₅, NH₄VO₃, and H₄V₂O. 10 At least one of V(OH)3, Na3VO4, or Na4V2O7. As an example, the vanadium source can be V2O3 or VO2.

[0054] In some specific embodiments, the hydrothermal reaction temperature is 170℃~190℃, and the time is 1h~30h. As an example, the hydrothermal reaction temperature can be 170℃, 180℃, 190℃, etc., or any value within the above range; no specific limitation is made here. The hydrothermal reaction time can be 1h, 5h, 10h, 15h, 20h, 30h, etc., or any value within the above range; no specific limitation is made here.

[0055] In some specific embodiments, the molar ratio of intermediate Mn(VO3)2, lithium source, phosphoric acid source, carbon source, and acid source is (1~5):(1~10):(1~10):(0.02~20):(2~20). As an example, the molar ratio of intermediate Mn(VO3)2, lithium source, phosphoric acid source, carbon source, and acid source can be 1:1:1:0.02:2, 2:3:5:10:12, 5:10:10:20:20, etc., or any ratio within the above range, without specific limitation.

[0056] In some specific embodiments, the molar concentration of intermediate Mn(VO3)2 in the mixture is 0.01 mol / L to 1 mol / L. As an example, the molar concentration of intermediate Mn(VO3)2 in the mixture can be 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, etc., or any value within the above range, and is not specifically limited here.

[0057] In some embodiments, the solvent includes water and / or an organic solvent. Specifically, the organic solvent includes alcoholic organic solvents or ketone organic solvents. As an example, the organic solvent may be ethanol or acetone.

[0058] In some specific embodiments, when the solvent is a mixture of water and an organic solvent, the volume of water is ≥40%. As an example, when the solvent is a mixture of water and an organic solvent, the volume of water can be 40%, 50%, or 60%.

[0059] In some specific embodiments, the lithium source includes, but is not limited to, at least one of lithium carbonate, lithium hydroxide, and lithium oxide.

[0060] In some specific embodiments, the phosphoric acid source includes, but is not limited to, at least one of ammonium dihydrogen phosphate, sodium hypophosphite, and ammonium pyrophosphate.

[0061] In some specific implementations, the acid source includes, but is not limited to, oxalic acid dihydrate, acetic acid, and benzoic acid.

[0062] In some specific embodiments, the carbon source includes, but is not limited to, at least one selected from polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan laurate, glucose, pitch, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinylpyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene, or aniline. As an example, the carbon source may be polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan laurate, or glucose. Preferably, at least one selected from polyoxyethylene sorbitan monooleate or polyoxyethylene sorbitan laurate is used; more preferably, a mixture of polyoxyethylene sorbitan monooleate and polyoxyethylene sorbitan laurate in a 1:1 mass ratio is used.

[0063] In this application, two environmentally friendly polysorbate ester nonionic surfactants were selected as carbon sources. Polyoxyethylene sorbitan monooleate (Tween 80) and polyoxyethylene sorbitan laurate (Tween 20) were composited, and the remaining materials (intermediate Mn(VO3)2, lithium source, phosphoric acid source, and acid source) were carbon-coated using a wet ball milling method. On the one hand, the emulsifying effect of polyoxyethylene sorbitan monooleate was utilized to enhance the carbon coating of LiMn during the synthesis process. 1-x V x PO4 and Li3V 2-y Mn y (PO4)3 (0≤x≤0.1, 0≤y≤0.15) particles are dispersed in a single process. After pyrolysis, the surfactant forms a uniform residual carbon layer on the particle surface, which hinders further particle agglomeration and refines the particles. This helps to shorten the lithium-ion transport distance, improve ionic conductivity, and increase the rate performance of the material. The residual carbon formed by the pyrolysis of polyoxyethylene dehydrated sorbitan laurate has a high degree of graphitization, which improves the electronic conductivity of the material. By selecting the above two surfactants to replace the traditional carbon source, their synergistic effect is utilized to improve ionic and electronic conductivity, thereby enhancing the electrochemical performance of the cathode material.

[0064] In some specific embodiments, the ball milling speed is 300 rpm to 400 rpm, and the time is 0.5 h to 9 h. As an example, the ball milling speed can be 300 rpm, 350 rpm, 400 rpm, etc., or any value within the above range; no specific limitation is made here. The ball milling time can be 0.5 h, 1 h, 3 h, 6 h, 9 h, etc., or any value within the above range; no specific limitation is made here. It should be noted that the core material LiMn in this application... 1-x V x PO4 and Li3V 2-y Mn y (PO4)3 (0≤x≤0.1, 0≤y≤0.15) is formed during ball milling.

[0065] In some specific embodiments, sintering is carried out under an inert atmosphere, and sintering includes pre-firing and baking. Pre-firing allows for sufficient adjustment of the atomic structure, making the reaction more complete, and also volatilizes the ash.

[0066] In some specific implementations, the preheating temperature is 250℃~450℃, and the time is 1h~6h. For example, the preheating temperature can be 250℃, 350℃, 450℃, etc., or any value within the above range; no specific limitation is made here. The preheating time can be 1h, 3h, 6h, etc., or any value within the above range; no specific limitation is made here.

[0067] In some specific embodiments, the calcination temperature is 650℃~750℃, and the time is 1h~12h. As an example, the calcination temperature can be 650℃, 700℃, 750℃, etc., or any value within the above range; no specific limitation is made here. If the calcination temperature is too high, the increase in oxygen vacancies in the crystal structure can easily cause crystal structure collapse; if the calcination temperature is too low, the crystal structure will be unstable.

[0068] The calcination time can be 1 hour, 3 hours, 6 hours, 9 hours, 12 hours, or any value within the above range; no specific limitation is made here. If the calcination time is too long, the increase in oxygen vacancies in the crystal structure will easily cause the crystal structure to collapse; if the calcination time is too short, the crystal structure will be unstable.

[0069] In some specific embodiments, the particle size of the ground product is 100nm≤Dv50≤50μm. As an example, the particle size Dv50 of the ground product can be 100nm, 500nm, 1μm, 10μm, 20μm, 50μm, etc., or it can be any value within the above range, without being specifically limited here.

[0070] Therefore, based on the above, this invention first prepares a Mn(VO3)2 precursor, and then grows LiMn in situ on the basis of the precursor. 1-x V x PO4 and Li3V 2-y Mn y (PO4)3 (0≤x≤0.1, 0≤y≤0.15), this method utilizes Mn(VO3)2, which simultaneously provides both manganese and vanadium sources. During phosphate formation, the crystal structures are in close contact, mixing at a smaller particle scale. During crystal growth, vanadium ions enter the lithium manganese phosphate unit cell, replacing some manganese atoms, and manganese ions enter the lithium vanadium phosphate unit cell, replacing some vanadium atoms, thus performing in-situ doping. This atomic doping reduces the surface energy of the material, resulting in a closer contact between the two materials. It also improves the electronic and ionic conductivity of lithium manganese phosphate. Compared to the conventional LiMnPO4 and Li3V2(PO4)3 composite, the closer contact makes it less likely for manganese to dissolve from the lithium manganese phosphate. The smaller-scale, closer contact significantly improves both electronic and ionic conductivity.

[0071] Based on the same inventive concept, this application provides a battery including a positive electrode sheet, the positive electrode sheet including a positive electrode material, the positive electrode material being the aforementioned positive electrode material or a positive electrode material prepared according to the aforementioned preparation method.

[0072] [Preparation of positive electrode sheet] The positive electrode material, conductive agent, and binder are mixed in a solvent to obtain a slurry. The slurry is then coated onto a current collector and dried to obtain a positive electrode sheet.

[0073] In some specific implementations, the mass ratio of positive electrode material, conductive agent, and binder is 95%~99%: 0.1%~%: 0.5%~3%.

[0074] In some specific embodiments, the current collector includes at least one of aluminum foil or nickel foil.

[0075] In some specific implementations, the coating thickness of the slurry is 10 μm to 200 μm.

[0076] In some specific implementations, after the positive electrode sheet is prepared, it can be cut into the required size by a cutting machine.

[0077] Because this battery contains a positive electrode sheet made of the positive electrode material provided in the embodiments of this application, it has the advantages of higher energy density, longer cycle life and faster charging speed.

[0078] In some embodiments, the battery further includes a negative electrode, an electrolyte, and a separator. That is, the battery includes a positive electrode, a negative electrode, an electrolyte, and a separator.

[0079] In this embodiment, the materials and structures of the negative electrode current collector, the conductive agent and the binder in the negative electrode active material layer are not limited, and negative electrode structures and components known in the art that can be used in secondary batteries can be selected.

[0080] In this embodiment, the type of separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.

[0081] It should also be noted that the battery in this application does not limit the specific material or type of electrolyte. Any components and types known in the art that can be used in secondary batteries can be selected, as long as the purpose of this application can be achieved.

[0082] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.

[0083] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0084] Example 1 1 mmol MnCl2·4H2O and 2 mmol NH4VO3 were dissolved in 10 mL and 20 mL of water, respectively. NH4VO3 was dissolved by stirring while heating at 50 °C. The MnCl2 solution was added dropwise to the NH4VO3 solution, and the mixture was stirred magnetically until homogeneous. The mixture was then subjected to a hydrothermal reaction at 180 °C for 18 h. After cooling, filtration, washing with water, and drying, a brown product, Mn(VO3)2, was obtained. 0.05 mol Mn(VO3)2, 0.06 mol lithium carbonate, 0.1 mol ammonium dihydrogen phosphate, 1.2612 g oxalic acid dihydrate, 0.2 g polyoxyethylene dehydrated sorbitan monooleate, 0.2 g polyoxyethylene dehydrated sorbitan laurate, 5 ml deionized water, and 2 ml anhydrous ethanol were mixed and ball-milled at 350 rpm for 4 h. The mixture was then dried to obtain a yellowish-white powder. The powder was placed in an alumina boat, sealed, and sintered at high temperature in an argon atmosphere. The mixture was pre-calcined at 350℃ for 2 h, calcined at 700℃ for 12 h, and then cooled to room temperature. The mixture was then ball-milled with agate grinding beads of 1 mm in diameter and a grinding bead to sample mass ratio of 20:1 for 1 h to obtain a black powder product (Dv50=5μ), which is the cathode material.

[0085] The scanning electron microscope (SEM) image of the cathode material can be found in the appendix of the instruction manual. Figure 1 ,Depend on Figure 1 It can be seen that the cathode material has a uniform particle size and the surface carbon material is thin and fine.

[0086] Example 2 The difference between Example 2 and Example 1 is that the hydrothermal reaction temperature is 170°C and the time is 20 hours.

[0087] Example 3 The difference between Example 3 and Example 1 is that the hydrothermal reaction temperature is 150°C and the time is 12 hours.

[0088] Example 4 The difference between Example 4 and Example 1 is that the hydrothermal reaction temperature is 210°C and the time is 24 hours.

[0089] Example 5 The difference between Example 5 and Example 1 is that polyoxyethylene dehydrated sorbitan monooleate was not added.

[0090] Example 6 The difference between Example 6 and Example 1 is that polyoxyethylene dehydrated sorbitan laurate was not added.

[0091] Example 7 The difference between Example 7 and Example 1 is that the addition of polyoxyethylene sorbitan monooleate and polyoxyethylene sorbitan laurate is replaced with glucose.

[0092] Example 8 The difference between Example 8 and Example 1 is that the calcination temperature is 800°C and the time is 6 hours.

[0093] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 did not contain polyoxyethylene dehydrated sorbitan monooleate and polyoxyethylene dehydrated sorbitan laurate, that is, Comparative Example 1 does not contain a carbon coating layer.

[0094] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses a simple 1:1 molar mixture of carbon-coated lithium manganese phosphate and lithium vanadium phosphate as the cathode material.

[0095] Performance testing 1. Battery manufacturing Positive electrode sheet: The positive electrode material prepared in each embodiment and comparative example is mixed with conductive agent and binder in a solvent (the mass ratio of positive electrode material, conductive agent and binder is 98%:0.5%:1.5%) and coated onto aluminum foil with a coating thickness of 180μm. The size of the positive electrode sheet is 96mm×51mm.

[0096] Negative electrode sheet: Graphite is used as the negative electrode active material. It is mixed with conductive agent and binder in a solvent (the mass ratio of graphite, conductive agent and binder is 97.5%:1%:1.5%) and coated on aluminum foil with a coating thickness of 140μm. After drying, pressing and other processes, the negative electrode sheet is made with a size of 100mm×55mm.

[0097] The diaphragm is made of Whatman GF / D glass fiber diaphragm.

[0098] Electrolyte: In a glove box filled with inert gas, ethylene carbonate and diethyl carbonate are mixed at a mass ratio of 1:1 to obtain an organic solvent. Then, lithium salt LiPF6 is dissolved in the organic solvent at a concentration of 1 mol / L to obtain the electrolyte.

[0099] Battery assembly: The positive electrode, modified separator, and negative electrode are stacked in sequence to obtain the battery cell. The stacked battery cell is hot-pressed and placed in an aluminum-plastic film for top and side sealing. Electrolyte is injected into the battery. The battery is then sealed after injection, with an injection coefficient of 3g / Ah. The packaged battery is then subjected to formation treatment.

[0100] 2. Perform electrochemical performance testing on the battery. (1) First coulombic efficiency test: The batteries prepared in each example and comparative example were tested for the first time under the test conditions of charging and discharging current of 1A / g, charging cut-off voltage of 2.5V and discharging cut-off voltage of 4V.

[0101] (2) Capacity retention rate test after 500 cycles: Take the batteries made in each example and comparative example, and repeat the test 500 times under the conditions of charging and discharging current of 1A / g, charging cut-off voltage of 2.5V and discharging cut-off voltage of 4V. Record the ratio of the discharge capacity of the 500th cycle to the discharge capacity of the first cycle as the capacity retention rate (Note: the higher the capacity retention rate, the longer the service life of the electrode).

[0102] (3) DC internal resistance (DCR) test: Charge to 4V with constant current and constant voltage at 0.33C, let stand for 30 minutes, then discharge with constant current at 0.33C for 90 minutes to adjust the state of charge to 50% SOC, let stand for 30 minutes, and then discharge with 2C current for 10 seconds. Record the voltage before and after discharge. Wherein, DCR = (V 放电前 -V 放电末期 ) / current.

[0103] The results of the above tests are shown in Table 1.

[0104] Table 1 Table 1 shows that different materials, hydrothermal reaction time, and reaction temperature all affect the initial efficiency and cycle performance of the material. The results indicate that a hydrothermal reaction temperature of 180℃ and a reaction time of 18 hours are optimal. Referring to Example 3, when the reaction temperature is too low, the capacity retention rate after 500 cycles is poor, and the DC internal resistance (DCR) is high. This may be because the low reaction temperature results in poor crystal structure stability. Referring to Example 4, when the reaction temperature is too high, the capacity retention rate after 500 cycles is poor, and the DC internal resistance (DCR) is high. This may be due to the collapse of the material structure caused by excessive oxygen vacancies at high temperatures. Referring to Example 5, using only polyoxyethylene sorbitan laurate as a carbon source to prepare the cathode material, the final 500-cycle capacity retention data was poor, and the DC internal resistance (DCR) was high. This was because the surfactant strength of polyoxyethylene sorbitan laurate was high, resulting in an excessively thick coating on the material surface. Referring to Example 6, using only polyoxyethylene sorbitan monooleate as a carbon source, the final 500-cycle capacity retention data was poor, and the DC internal resistance (DCR) was high. This was because the coating of polyoxyethylene sorbitan monooleate had defects. Referring to Example 7, using glucose as a carbon source, the final 500-cycle capacity retention data was poor, and the DC internal resistance (DCR) was high. This was because the glucose coating had uneven thickness and poor contact stability with the material.

[0105] The cathode material in Comparative Example 1, which does not contain a carbon coating layer, exhibits extremely poor initial coulombic efficiency and 500-cycle capacity retention, along with a significantly increased DC internal resistance (DCR), indicating that the carbon coating layer has a significant impact on material performance.

[0106] Comparative Example 2 simply mixed lithium manganese phosphate and lithium vanadium phosphate with carbon coating at a 1:1 molar ratio. The initial coulombic efficiency, 500-cycle capacity retention, and DC internal resistance (DCR) results were all unsatisfactory. This indicates that partial Mn and V doping resulted in tighter contact between the core materials, reducing their surface energy and making the carbon coating more stable and less prone to detachment during long cycles. This effectively prevents electrolyte failure caused by direct contact between the core material and the electrolyte, avoids polarization of the cathode material, and improves the cycle stability of the cathode material. Compared to the conventional mixture of LiMnPO4 and Li3V2(PO4)3, the tighter contact makes it less likely for manganese in lithium manganese phosphate to dissolve. The smaller-scale, closer contact significantly improves electronic and ionic conductivity, whereas simple mixing cannot achieve the synergistic effect of co-doping.

[0107] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0108] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0109] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0110] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material, characterized in that, The cathode material includes: a core and a carbon coating layer covering at least a portion of the surface of the core; The kernel includes LiMn 1-x V x PO4 and Li3V 2-y Mn y (PO4)3; Where 0 < x ≤ 0.1, 0 < y ≤ 0.15; The method for preparing the cathode material includes the following steps: mixing a manganese source solution and a vanadium source solution and then carrying out a hydrothermal reaction to obtain the intermediate Mn(VO3)2; The intermediate Mn(VO3)2, lithium source, phosphoric acid source, carbon source and acid source are mixed in a solvent to obtain a mixture, which is then ball-milled, sintered and ground to obtain the cathode material. The carbon source includes polyoxyethylene sorbitan monooleate and polyoxyethylene sorbitan lauryl ester.

2. The cathode material according to claim 1, characterized in that, The LiMn 1-x V x PO4, Li3V 2-y Mn y The molar ratio of (PO4)3 to carbon is 1:1:(0.01~0.1).

3. The method for preparing the cathode material according to any one of claims 1 to 2, characterized in that, Includes the following steps: The manganese source solution and the vanadium source solution were mixed and subjected to a hydrothermal reaction to obtain the intermediate Mn(VO3)2. The intermediate Mn(VO3)2, lithium source, phosphoric acid source, carbon source and acid source are mixed in a solvent to obtain a mixture, which is then ball-milled, sintered and ground to obtain the cathode material. The carbon source includes polyoxyethylene sorbitan monooleate and polyoxyethylene sorbitan lauryl ester.

4. The method for preparing the cathode material according to claim 3, characterized in that, The solvent in the manganese source solution includes water and / or organic solvents; And / or, the molar concentration of the manganese source solution is 0.03 mol / L to 0.5 mol / L; And / or, the manganese source includes at least one of MnCl2, MnSO4, Mn(NO3)2 or Mn3(PO4)2.

5. The method for preparing the cathode material according to claim 3, characterized in that, The solvent in the vanadium source solution includes water and / or organic solvents; And / or, the molar concentration of the vanadium source solution is 0.06 mol / L to 1 mol / L; And / or, the vanadium source includes V2O3, VO2, V2O4, V2O5, NH4VO3, H4V2O 10 At least one of V(OH)3, Na3VO4 or Na4V2O7.

6. The method for preparing the cathode material according to claim 3, characterized in that, The hydrothermal reaction is carried out at a temperature of 170℃ to 190℃ for a duration of 1 hour to 30 hours.

7. The method for preparing the cathode material according to claim 3, characterized in that, The molar ratio of the intermediate Mn(VO3)2, the lithium source, the phosphoric acid source, the carbon source, and the acid source is (1~5):(1~10):(1~10):(0.02~20):(2~20). And / or, the molar concentration of the intermediate Mn(VO3)2 in the mixture is 0.01 mol / L to 1 mol / L; And / or, the solvent includes water and / or organic solvents.

8. The method for preparing the cathode material according to claim 3, characterized in that, The ball milling speed is 300 rpm to 400 rpm, and the time is 0.5 h to 9 h; And / or, the sintering is carried out under an inert atmosphere, and the sintering includes pre-firing and baking; The pre-firing temperature is 250℃~450℃, and the time is 1h~6h; The roasting temperature is 650℃~750℃, and the time is 1h~12h; And / or, the particle size of the ground product is 100nm≤Dv50≤50μm.

9. A battery comprising a positive electrode sheet, said positive electrode sheet comprising a positive electrode material, characterized in that, The cathode material is the cathode material according to any one of claims 1 to 2 or the cathode material prepared by the preparation method according to any one of claims 3 to 8.

Citation Information

Patent Citations

  • Preparation method of lithium manganese phosphate-lithium vanadium phosphate composite

    CN104300110A

  • Preparation method of lithium manganese phosphate-lithium vanadium phosphate composite material

    CN104347852A